Composición química de ejemplares de la almeja taquilla Mulinia edulis de bancos naturales del norte y sur de Chile - Abarca, Alejandro; Toledo, Pedro; Oliva, Doris (Revista de Biología Marina y Oceanografía, 2018)
Chemical composition, morphometry and meat yield of Mulinia edulis, were analyzed for two size groups and two locations. The clams were taken from natural beds, one located in the north (Peñuelas; 29°55´S) and the second in the south (Putemún; 42°25´S) of Chile. The first size group corresponds to legal catch size (>5.5 cm) and the second to ‘baby clams’ (<4 cm). The standardized AOAC methodology was used to determine the proximal values. Results show that M. edulis is a species with high water content in its tissues (>80%), high protein value (>11%) and low fat content (<2%). Proteins and total lipids were significantly higher in Peñuelas than Putemún. Furthermore, the water content (humidity) was higher in Putemún than in Peñuelas, and in baby clams than in large clams. Meat yield was higher in the Peñuelas clams (>20%) than those of Putemún (<20%). Finally, the clam M. edulis, independent of the origin and size, is a healthy food due to its low lipid content, but small clams (= baby clams) have a higher meat yield.